The Evolution of Labor Markets - Huberman, Michael (The Routledge Handbook of Modern Economic History, 2012)
Informed by labor economics and labor history, the economic history of labor markets is an alternative and unified approach to study the wage and employment relation. This broad field encompasses the nature, organization, and conditions of work, as well as the non-wage compensation labor earned. It is an alternative approach because, unlike the economics’ textbook model, the economic historian does not perceive the labor market as static. Rather, economic history provides a framework to examine the feedback mechanisms – the dynamic relation – between labor markets and technological change, business organization, government regulation, product markets, and the preferences of participants themselves. Put differently, history provides rich examples of the many margins of adjustment in labor markets across space and time, in addition to wage and employment dimensions.

Are Canada's Labour Standards Set In The Third World? Historical Trends And Future Prospects - Huberman, Michael (C.D. Howe Institute, 2005)
This framework seems to mesh with the economic history of Canada's two central provinces, Ontario and Quebec, around the mid-twentieth century. Quebec was clearly the labour-abundant province, Ontario the capital-abundant region. Many labour reforms were first introduced in Ontario because it was the wealthier region. Since the two regions remained relatively large trading partners - as they were as long as tariffs protected Canadian industry - Quebec had an incentive to match Ontario's labour standards. ( 16) Thus, as long as Canada had effective tariff protection, producers and workers in the export industries in both regions benefited from rising labour standards, while consumers all across the country suffered, a result that was clearly not in the general interest. Since there was an incentive to overprotect, Ottawa's intervention in this area did not come up against provincial antagonism. In fact, sub-national authorities would have welcomed a central authority to coordinate standards. Richard Block and Karen Roberts (2000) provide the most exhaustive study of labour standards as they were in the late 1990s. Their results show a more consistent pattern. They divide provincial, territorial and federal labour standards for 1998 into nine categories reproduced in Table 3. ( 19) Each category is itself a composite of several indicators. Thus the category "paid time off" comprises, but is not restricted to, the variables found in Table 2. The calculation of the index value for each category followed a two-step procedure. First, individual provisions or labour standards in each category were given an index value that was greater the higher the level of employee protection; secondly, each provision was given a weight to represent its importance in its category. ( 20) There is some degree of arbitrariness in all this but, given the large number of standards included in the exercise, it would be expected that errors of commission would cancel out. The first two columns of Table 4 report the sum of the index values (nine labour standards and employment insurance) and the sum of the index values after each provision was deflated by an estimate of coverage. The higher the value, the greater the degree of labour protection. The last column of Table 4 gives the ranking of labour protection of each province and territory in North America in descending order. ( 21 ) Jurisdiction Minimum wage Over-time Paid time off Worker's compensation Federal 4.28 10.00 6.27 6.77 Alberta 1.52 (12) 7.28 (7) 7.61 (2) 6.69 (10) British Columbia 7.04 (1) 10.00 (1) 6.27 (4) 8.58 (3) Manitoba 2.44 (6) 10.00 (1) 5.89 (8) 6.54 (11) New Brunswick 2.44 (6) 3.21 (12) 5.38 (11) 5.99 (12) Newfoundland 2.44 (6) 4.57 (11) 5.53 (10) 7.25 (9) North West Territories 6.12 (3) 10.00 (1) 6.27 (4) 8.82 (1) Nova Scotia 2.44 (6) 1.85 (1) 5.71 (9) 7.32 (8) Ontario 6.12 (3) 7.28 (7) 6.07 (7) 7.64 (7) Prince Edward Island 2.44 (6) 5.92 (10) 5.20 (12) 7.72 (6) Quebec 6.12 (3) 7.28 (7) 7.23 (3) 8.35 (5) Saskatchewan 2.44 (6) 10.00 (1) 9.11 (1) 8.66 (2) Yukon 7.04 (1) 10.00 (1) 6.27 (4) 8.43 (4) Jurisdiction Collective Employment Unjust Occupational Advance notice bargaining equity discharge safety of plant closing and health largescale layoffs Federal 6.00 9.00 7.00 4.33 5.53 Alberta 6.00 (9) 8.10 (11) 7.00 3.07 (5) 0.00 (11) British Columbia 10.00 (1) 8.60 (5) 7.00 3.20 (2) 7.89 (1) Manitoba 9.00 (3) 9.10 (1) 7.00 3.13 (4) 6.03 (5) New Brunswick 8.00 (8) 8.10 (11) 7.00 2.11 (10) 5.71 (6) Newfoundland 9.00 (3) 8.60 (5) 7.00 2.08 (11) 5.03 (8) North West Territories 6.00 (9) 9.00 (3) 7.00 2.18 (8) 3.21 (10) Nova Scotia 6.00 (9) 9.10 (1) 7.00 2.18 (8) 6.37 (4) Ontario 9.00 (3) 8.50 (9) 7.00 3.24 (1) 7.03 (2) Prince Edward Island 9.00 (3) 8.60 (5) 7.00 1.87 (12) 0.00 (11) Quebec 10.00 (1) 9.00 (3) 7.00 2.63 (7) 4.50 (9) Saskatchewan 9.00 (3) 8.60 (5) 7.00 3.00 (6) 6.87 (3) Yukon 6.00 (9) 8.50 (9) 7.00 3.17 (3) 5.21 (7)
Num Pages: 1-28 Place: Toronto, Canada
Keywords: Canada; Economic history; Jurisdiction; Labour; Labour law; Ontario; Quebec; Tariff; Unemployment benefits

Working Hours of the World Unite? New International Evidence of Worktime, 1870–1913 - Huberman, Michael (The Journal of Economic History, 2004)
This article constructs new measures of worktime for Europe, North America, and Australia, 1870–1913. Great Britain began with the shortest work year and Belgium the longest. By 1913 certain continental countries approached British worktimes, and, consistent with recent findings on real wages, annual hours in Old and New Worlds had converged. Although globalization did not lead to a race to the bottom of worktimes, there is only partial evidence of a race to the top. National work routines, the outcome of different legal, labor, and political histories, mediated relations between hours and income.

An Economic and Business History of Worksharing: The Bell Canada and Volkswagen Experiences - Huberman, Michael (Business and Economic History, 1997)

Piece Rates Reconsidered: The Case of Cotton - Huberman, Michael (The Journal of Interdisciplinary History, 1996)

Some Early Evidence of Worksharing: Lancashire before 1850 - Huberman, Michael (Business History Review, 1995)
The first generation of enterprises during the industrial revolution had made sizeable investments in new machinery and plant, and to amortise these fixed costs it is widely believed that firms worked long hours, regardless of the state of trade. A detailed study of Lancashire textile firms in 1841 shows this picture to be inaccurate. Short-time working was a common response of firms, especially large ones, during cyclical downturns in the nineteenth century. Firms used collective output cuts as a means to protect the wage lists they had negotiated with workers. The lists also promoted and preserved the regional basis of the industry. As for workers, they saw short-time as a means to protect their jobs and the standard relation between effort and pay. Enforced by sanctions on firms that broke output agreements, short-time evolved into a rule of thumb in the Lancashire textile industry.
_eprint: https://doi.org/10.1080/00076799500000125

Industrial Relations and the Industrial Revolution: Evidence from M'Connel and Kennedy, 1810–1840 - Huberman, Michael (Business History Review, 1991)
Using the record books of M'Connel and Kennedy, a leading cotton-spinning firm in Manchester, this article traces the development of managerial strategies to elicit effort from workers during the Industrial Revolution. Contrary to the conventional wisdom, the firm had difficulty in extracting effort from its workers, who were unwilling to increase output without capturing some of the gains through wage adjustments. Since spinners controlled the work organization, M'Connel and Kennedy had to accommodate workers' demands for stable piece rates, which were codified in the Manchester list of prices of 1829.

Vertical Disintegration in Lancashire: A Comment on Temin - Huberman, Michael (The Journal of Economic History, 1990)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0022050700037244/resource/name/firstPage-S0022050700037244a.jpg

Invisible Handshakes in Lancashire: Cotton Spinning in the First Half of the Nineteenth Century - Huberman, Michael (The Journal of Economic History, 1986)
In Lancashire cotton spinning in the heyday of laissez-faire capitalism the labor market did not operate as an auction market. Evidence on piece-rate flexibility, length of tenure, and seniority is consistent with Okun's contract approach. Both workers and firms incurred initial set-up costs. Workers wanted to protect their initial investments in training, and firms, faced with a labor supply that varied in reliability and regularity, had a desire to cover initial hiring and tryout costs. The need to maintain long-term attachments had implications for wage and employment adjustment and the age structure of the labor force.

Odd couple: international trade and labor standards in history - Huberman, Michael (Yale University Press, 2012)
Section: xii, 237 p. : ill ; 25 cm.

The 100-year Welfare State? - Huberman, Michael (Books & Ideas, 2014)

One world of labour regulation, two worlds of trade: examples of Belgium and Brazil - Huberman, Michael (European Review of Economic History, 2013)

New evidence on the rise of trade and social protection - Huberman, Michael (CEPR, 2009)
Globalisation is often accused of unleashing a race to the bottom in labour regulation and social protection. The evidence suggests otherwise. This column explains how, historically, trade itself was a path to better labour regulation and social entitlements.

Ticket to trade: Belgian labour and globalization before 19141 - Huberman, Michael (The Economic History Review, 2008)
Standard trade theory, as invoked by political scientists and economists, would anticipate that workers in Belgium, a small Old World country, rich in labour relative to land, were in a good position to benefit from the wave of globalization before 1914. However, wage increases remained modest and ‘labour’ moved slowly towards adopting a free-trade position. Beginning in 1885, the Belgian labour party backed free trade, but its support was conditional on more and better social legislation. Belgian workers' wellbeing improved in the wave of globalization, but the vehicle was labour and social legislation and not rising wages.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1468-0289.2007.00396.x

Shame and Guilt in Lancashire: Enforcing Piece Rate Contracts - Huberman, Michael (CIRANO Working Papers Scientific Series, 1999)

Escape from the Market: Negotiating Work in Lancashire - Huberman, Michael (Cambridge University Press, 1996)
At the outset of the industrial revolution the Lancashire labour market was a model of thoroughgoing competition. Wages adjusted quickly and smoothly to changes in the demand for and supply of labour. Within two generations, however, workers and firms had retreated from the market. Instead of busting wages, firms paid fixed rates; instead of breaking ties on short notice, workers sought longer-term associations. Social norms - doing the right thing - protected and preserved the fresh labour market arrangements. This book explains the causes and effects of changes in the labour market in the context of developments in labour economics and fresh research in social and economic history.
Google-Books-ID: 6p1_7DSl9lwC
Keywords: Business & Economics / Economic History; Business & Economics / Economics / General; Business & Economics / Industrial Management; Business & Economics / Infrastructure; Business & Economics / Labor / Wages & Compensation

Testing for the “Conscientious Withdrawal of Efficiency”: Evidence from the Industrial Revolution - Huberman, Michael (Historical Methods: A Journal of Quantitative and Interdisciplinary History, 1993)

How did labor markets work in lancashire? more evidence on prices and quantities in cotton spinning, 1822–1852 - Huberman, Michael (Explorations in Economic History, 1991)
Using yarn prices and output as proxies for wages and employment, this paper asks how cotton spinning firms in the heyday of industrialization responded to demand shocks. The evidence is consistent with a two-sector efficiency wage model composed of large and small firms. Large firms incurred monitoring costs on their new technology. To eliminate shirking, they paid efficiency wages and laid off workers when faced by a reduction in demand. In small firms technical change was slower, and since monitoring was not a problem, they cut wages. Over the period, the number of small firms declined and layoffs increased.

The economic origins of paternalism: Reply to Rose, Taylor and Winstanley - Huberman, Michael M. (Social History, 1989)

Against the Grain: Spanish Trade Policy in the Interwar Years - Betrán, Concepción; Huberman, Michael (The Journal of Economic History, 2022)
We study the effects of domestic conflict and external shocks on Spanish trade policy in the interwar period. Our account mobilizes a new granular dataset on exports and imports, and good-country level information on tariffs, trade agreements, and quotas. Into the Depression, the mainstay of policy was the tariff. The establishment of the Second Republic in 1931 was a turning point in policymaking. The new regime initiated bilateral trade negotiations. The Republic’s dilemma was to find countries willing to exchange market access. In a daunting international environment, the Spanish case offers a poignant reminder of the perils of going against the grain.

European economic integration and the labour compact, 1850–1913 - Huberman, Michael; Lewchuk, Wayne (European Review of Economic History, 2003)
Globalisation was a fact of life in Europe before 1913, but as trade shares increased, so did wage and employment instability. Faced by growing pressure from workers, national authorities established labour compacts – a packet of labour market regulations and social insurance programmes – that defended workers against the risks they faced in and outside the factory. The labour compact provided workers with insurance because it compressed wage structures. We construct an index of labour market regulations and social insurance schemes for seventeen European countries and find that the extent of the labour compact varied with the level of openness. We conclude that the labour compact gave workers reason to support free trade because it protected them from external risk. Contrary to the received view, globalisation before 1913 was compatible with state intervention. Our findings are consistent with Rodrik's and Agell's for the period after 1945.

Changing Attitudes toward Worksharing: Evidence from Quebec - Huberman, Michael; Lanoie, Paul (Canadian Public Policy / Analyse de Politiques, 2000)
Cet article évalue cinq expériences récentes sur le partage du travail au Québec depuis 1994: Bell Canada, Alcan, Papier Scott, Sico et le Ministère de l'environnement et de la faune. Basées sur des évidences de sondages qui démontrent que les heures de travail désirées tendent vers une approximation des heures de travail actuelles, des études antérieures ont souligné des doutes en ce qui concerne les chances de succès des initiatives pour le partage du travail. Par contre, dans les cas que nous avons étudiés les taux de participation dans les programmes volontaires de partage de travail étaient élevés, particulièrement lorsque le coût d'opportunité (les salaires perdus) des travailleurs n'était pas élevé et lorsque les travailleurs avaient déjà été exposé à des expériences de temps de travail réduit et flexible. Les initiatives de partage du travail ont rencontré moins de succès lorsqu'elles étaient obligatoires. Les programmes étudiés suggèrent que les réponses à l'offre de travail sont importantes lors de la création de politiques. Les gouvernements ont un rôle dans la création de politiques qui rendent le partage du travail plus attrayant aux travailleurs en plus de changer les attitudes des travailleurs envers le partage du travail. Nos résultats sont en accord avec les recommendations du Groupe consultatif sur le temps de travail du gouvernement fédéral. /// This paper evaluates five recent experiences of worksharing in Quebec since 1994: Bell Canada, Alcan, Scott Paper, Sico, and the Ministère de l'environnement et de la faune. Based on survey evidence showing that desired work hours tend to approximate actual work hours, previous studies have raised doubts about the likelihood of successful worksharing initiatives. However, in the cases we have studied, participation rates in voluntary worksharing programs were high, especially where the worker's sacrifice (lost wages) was not great and where workers had previous experience with reduced and flexible worktime. Worksharing initiatives were less successful when they were mandatory. The programs studied point to the importance of labour-supply responses in policy design. Governments have a role to play in designing policy that makes worksharing more attractive to workers and then changes their attitudes toward it. Our findings are consistent with the recommendations of the federal government's Advisory Group on Working Time.

L’influence de la science économique sur les historiens : une analyse de deux revues canadiennes d’histoire (1970-1996) - Dupré, Ruth; Huberman, Michael (L'Actualité économique, 2000)
Social sciences recently witnessed an increase in multidisciplinary studies. Economists are part of this movement. Do they have an impact on other disciplines? Few studies are concerned with the transfer of knowledge from one discipline to another. Our paper tries to shed some light on this issue in the specific case of the contribution of economics to historical research in Canada in the last three decades. Is the use of economic tools widespread? Does it follow an upward trend over the period? Is it related to research topic, period treated or historiographical tradition? Is there a difference between Anglophone and Francophone historians? These are some of the questions explored.

La famille ouvrière dans une communauté minière du sud du pays de Galles, Treherbert, 1861-1891 - Poulin, André (Université de Montréal, 1996)

International competition in the first wave of globalization: new evidence on the margins of trade - Betrán, Concepción; Huberman, Michael (The Economic History Review, 2016)
We pose a seemingly ageless question in economic history. To what extent did new entrants in the late nineteenth-century cotton-textile industry threaten the customary markets of the European core? Exploiting a newly constructed dataset on textile imports to Spain, we find that as trade costs fell, new rivals began to sell a greater variety of products. Along this dimension, competition can be said to have increased. In response, producers in Europe adjusted the type and number of goods exported. By 1914, specialization mapped onto endowments of skilled labour, capital, and access to raw materials. While firms in new industrializing countries exported low-end varieties, incumbents in the core shipped high-end goods, unit values increasing with levels of development.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/ehr.12115

Le choix entre la natalité, le travail et l'éducation lors de la Révolution industrielle anglaise : le rôle des femmes - Drouin, Isabelle (Université de Montréal, 2001)
Keywords: Histoire

La politique russe de la Grande-Bretagne, 1918-1922 : pressions politiques, économiques et intellectuelles - Durivage, Stéfanie (Université de Montréal, 2002)
Keywords: Histoire

Les répercussions du plan Marshall sur les comportements économiques du Canada durant la période de l'après-guerre - Grandmaison, Mathieu (Université de Montréal, 2012)
The postwar years brought many challenges to the Canadian economy in terms of trade policies. Indeed, in the years between 1945 and 1950, Canada experienced growing trade imbalances as imports from the United States market reached new peaks and exports to the United Kingdom decreased dramatically due to financial exhaustion caused by the war. These developments soon raised concerns as the country was faced with the prospect of foreign reserves depletion, a situation mainly caused by the productivity gap existing between the economies of the two sides of the Atlantic. The American sponsored European Recovery Program or Marshall Plan was met with enthusiasm in Ottawa as it intended to restore economic viability of the European markets as well as to establish a multilateral trade system based on non-discriminatory trade practices. The international tensions of the nascent Cold War were to limit these achievements as the need for a strong Europe dictated the elimination of restrictive trade practices between European commercial partners without giving equal treatment to transatlantic trade relations. However, the conflictual Cold War context was to offer an alternative strategy to the Canadian’s quest for dollars, for Washington’s collective security concerns paved the way to closer economic cooperation and privileged access to Canadian exports of strategic materials and other defence related commodities in the American market. The Marshall Plan was a key element of the procurement mechanism of the NATO country whose demand alleviated the pressure on Canadian foreign reserves through greater exports to the United Stated.
Keywords: Cold War; Collective security; Commerce multilatéral; Currency area; Dollars shortage; Economic History; European reconstruction; GATT; Guerre froide; Histoire économique; History - Canadian / Histoire - Canadienne (UMI : 0334); Libéralisation commerciale; Multilateral trade; NATO; OTAN; Pénurie de dollars; Reconstruction de l'Europe; Sécurité collective; Trade liberalization; Zones monétaires

Construire un système réglementaire : l'état et l'industrie télégraphique au Canada, 1846-1916 - Mauras, Éric (Université de Montréal, 2009)
Keywords: Canada; Histoire; History; Regulation; Réglementation; State; Telecommunications; Telegraph; Télécommunications; Télégraphe; État

Aux origines du lobbyisme en France : le cas de l’industrie lainière au XVIIIe siècle - Minel, Flavian (Université de Montréal, 2020)
At the end of the 17th century, in Europe, a new economic discourse emerged: mercantilism. The result was a growing control by the royal administration over the countries’ industries and economy. This economic system dominated the first half of the 18th century before gradually weakening in the face of the rise of economic liberalism. Among the major industries at the time was the wool industry, which was relatively dispersed throughout the country. There was still a certain industrial concentration in certain généralité mainly in the north of France and in the south with the Languedoc region. These two regions constitute the main points of our study. The goal then is to understand how the geographic factor influences the formation and success of lobbies in the wool industry in a century of evolution of economic thinking. The first case study relates to the study of the wool industry in the Languedoc which opposes the economic privileges obtained by Marseille from the royal administration. The latter had exclusive rights to trade with the Levant region, the main outlet for Languedoc wool production. Huge protests and oppositions ensued between the two protagonists in order to defend the economic interests of each other. Finally, our second case study leads us to analyze the economic consequences of the signing of the Franco-British trade treaty in 1786. The latter had a huge consequence on the wool industry in the north of France. It the follow the emergence of a lobby in the wool industry demanding for a modification of the treaty. In reality this agreement materialized an opposition between two different kinds of pressure groups: the first one coming from a rural environment living primarily from agriculture; the second one coming from a mainly industrialized urban environment.
Keywords: 18th century; England and French Commercial agreement of 1786; France XVIIIe siècle; Groupe de pression; History - Modern / Histoire - Moderne (UMI : 0582); Industrial polemic; Industrie lainière; Levant; Liberalism economic; Libéralisme économique; Mercantilism; Mercantilisme; Polémique industrielle; Pressure groups; Traité commercial franco-britannique 1786; Wool industry

La "révolution agraire" de l’Écosse, 1755-1815 : une construction historiographique? : étude de cas sur l’Aberdeenshire - Sylvestre, Nicolas (Université de Montréal, 2010)
L’Écosse du XVIIIe siècle connaît de grands changements qui seront à l’aune des transformations socio-économiques sous-tendant sa Révolution industrielle. L’historiographie sur le sujet est divisée entre deux visions du développement – nommées pour le bienfait de cette étude traditionnelle et révisionniste – à savoir si ces transformations valident la notion d’une « révolution agraire ». Cette étude propose une recension de ces deux courants et propose d’appliquer leur analyse sur une région circonscrite, l’Aberdeenshire. À l’aide de l’Old Statistical Account, source majeure pour l’étude de l’histoire moderne écossaise, nous tenterons de démontrer que le caractère particulier du développement des régions ne correspond pas à l’application des conclusions nationales. Nous accorderons une attention spéciale à la propriété foncière, à l’impact des enclosures et à la temporalité des changements. De par ses spécificités, et son retard de modernisation agraire et agricole, nous croyons que la région suit le schéma dressé par les historiens révisionnistes, c.-à-d. des changements structurels s’étendant sur un temps long et ne s’inscrivant pas directement dans la période 1755-1815, traditionnellement désignée comme « révolution agraire ». Il s’agirait plutôt d’une adaptation partielle et originale des nouvelles idées mises de l’avant par les protagonistes de la modernisation.
Keywords: Aberdeenshire; Agriculture; Développement économique; Economical development; History - European / Histoire - Européenne (UMI : 0335); Old Statistical Account; Scotland; XVIIIe siècle; XVIIIth century; Écosse

Red Vienna: A Social Housing Experiment, 1923–1933 - Holzner, Mario; Huberman, Michael (The Journal of Interdisciplinary History, 2022)
The moderating effects of World War I on wealth and income inequality varied with the belligerents. In Austria, the state embraced austerity measures to eliminate hyperinflation and respect commitments to the League of Nations. To fill the void, the Social Democratic Workers’ Party (sdap) turned to its political stronghold in Vienna to advance its agenda of social spending and progressive taxation—Red Vienna’s signature program. The use of an electoral-cycle model finds that the construction of new buildings increased the party’s share of votes in municipal elections. The program mobilized support of young families in search of affordable and quality housing, also attracting the endorsement of the middle classes and elites, despite the higher tax burden imposed on them. The physical attributes of the new buildings and related investments, such as in schools, hospitals, and city infrastructure, benefited the entire population of Vienna.
Number: 1

Les anciens combattants canadiens-français de la Première Guerre mondiale et leur réintégration professionnelle - Bouchard, Carl; Huberman, Michael (Histoire sociale / Social History, 2020)
Le présent article donne un nouvel éclairage sur la réintégration dans le marché du travail des anciens combattants francophones québécois de la Première Guerre mondiale. En exploitant les dossiers personnels des combattants et les informations sur les salaires et les professions des recensements de 1911 et 1921, les auteurs examinent si les soldats de retour au pays ont eu de meilleurs résultats sur le marché du travail que les non-soldats. Les résultats tendent à montrer que l'acquisition de capital social et humain agit positivement sur la réintégration des anciens combattants, l'ampleur de cette amélioration dépendant de l'âge, de la durée du service, du statut des soldats (volontaires ou conscrits), de la profession, du lieu de résidence et du fait que les recrues ont servi en Europe ou sont restées au Canada.
Number: 109

Unintended consequences: International trade shocks and electoral outcomes during the Second Spanish Republic, 1931–1936 - Betrán, Concepción; Huberman, Michael (Explorations in Economic History, 2023)
An intractable domestic conflict between forces on the right and the left roiled the Second Spanish Republic. We claim that international trade shocks exacerbated political instability. Leveraging an exposure design and disaggregated trade and employment data, we study the effects of import and export exposure on vote shares of parties and coalitions in the Republic's three elections, 1931, 1933, and 1936. An increase in import exposure had a modest effect on election outcomes. The primary vector of change was the disruption in export markets caused by the world depression and discriminatory trade practices, most importantly the United Kingdom's adoption of imperial preference. Trade dislocation harmed the left and benefitted the right. If trade had remained at 1928 levels, our projections show that the Popular Front would have gained a clear and comfortable majority in the decisive 1936 election.
Keywords: Electoral outcomes; Interwar Europe; Political extremism; Second Spanish Republic; Trade shocks

The times they are not changin’: Days and hours of work in Old and New Worlds, 1870–2000 - Huberman, Michael; Minns, Chris (Explorations in Economic History, 2007)
This paper brings a historical perspective to debates on worktime differences across OECD countries, exploiting new data sets on hours of work per week, and days and hours of work per year between 1870 and 2000. We contest the popular view that the divergence in worktimes between Europe and North America and Australia is a recent phenomenon. Since 1870 the decline in weekly and annual hours was consistently greater in the Old World; the New World has had fewer days off for the last 130years. Labor power and inequality, held to be important determinants of worktime after 1970, had comparable effects in the period before 1913. We find that given their levels of income in 1870 New World workers supplied relatively too many hours of work.
Keywords: Comparative economic history; Hours of work; Labor supply; Vacation days

Hope against Hope: Strike Activity in Canada, 1920–1939 - Huberman, Michael; Young, Denise (Explorations in Economic History, 2002)
The received view is that, across countries and time, strike dimensions trace an empirical regularity. The incidence and duration of contract strikes move in opposite directions over the business cycle: incidence is procyclical and duration countercyclical. The Canadian experience in the interwar years was different. Strike incidence was independent of the business cycle and strike durations fell steadily over the period. A distinct pattern emerged. The 1920s saw a decline in strike activity and steady losses for workers; in the 1930s strike activity gained momentum and there were more worker wins. Our interpretation of this extraordinary episode is based on a new data set collected for the period 1920 to 1939. We evaluate strikes in the context of a war-of-attrition model and estimate the probability of strike outcomes (success, failure, or compromise) and capitulation times (for firms and workers) as functions of firm and striker characteristics. We find that workers capitulated first in the 1920s because firms used replacement workers as part of a larger strategy to break the union movement. In the 1930s, it was firms' turn to capitulate first because they had cut back on resources to fight strikes, even as workers became more belligerent.
Keywords: Canadian economic history; labor history; strike activity; war-of-attrition model

Occupational Gender Segregation: Public Policies and Economic Forces - Fortin, Nicole; Huberman, Michael (CIRANO, 2001)

Cross-Border Unions: Internationals in Canada, 1901–1914 - Huberman, Michael; Young, Denise (Explorations in Economic History, 1999)
Debate on the role of international unions (unions with headquarters in the United States) in Canada is longstanding. One school of thought maintains that internationals have weakened Canada's union movement; another view holds that international and national unions acted in concert and increased the number of disputes and the likelihood of workers' victory. Using a newly created data base of strike dimensions for the period before World War I, the key years of union growth in Canada, we test these opposing views in a competing-risks framework. We find that internationals did not weaken Canada's union movement; nor did the two union types act in concert. Instead, internationals were absorbed in Canada's industrial relations framework.

Globalization and Worker Welfare in Late Nineteenth Century Europe - Huberman, Michael; Lewchuk, Wayne (CIRANO Working Papers Scientific Series, 1999)
Keywords: =CL

Worksharing in Québec: Five Case Studies - Huberman, Michael; Lanoie, Paul (CIRANO Working Papers Scientific Series, 1998)
This paper evaluates five recent experiences of worksharing in Québec since 1994: Bell Québec, Alcan, Scott Paper, the Ministère de l'Environnement et de la Faune and Sico. Participation in voluntary worksharing programs was high where workers' sacrifice (lost wages) was not great and where workers had previous experience with shorter or flexible work hours. Where worksharing was mandatory programs were less successful. We draw out implications for policy. To achieve higher participation rates and to give workers experience with shorter hours, governments can play a positive role in financing or kick-starting worksharing programs. Cette étude évalue cinq expériences récentes de partage du travail au Québec depuis 1994 : Bell Québec, Alcan, Les papiers Scott, le Ministère de l'Environnement et de la Faune, et Sico. Le taux de participation aux programmes de partage du travail offerts sur une base volontaire était élevé dans les entreprises où les sacrifices que devaient consentir les travailleurs (les pertes salariales) n'étaient pas considérables et dans celles où les travailleurs avaient déjà fait l'expérience d'un horaire de travail flexible ou réduit. Dans les cas où le partage du travail était imposé, les programmes ont remporté moins de succès. Nous déduisons des conséquences en matière de politique publique. Entre autres, pour atteindre des taux de participation plus élevés et initier les travailleurs à un horaire réduit, les gouvernements peuvent jouer un rôle positif en finançant ou en aidant à démarrer des programmes de partage du travail.

Le partage de l'emploi: solution au chômage ou frein à l'emploi? - Huberman, Michael; Lacroix, Robert (Presses de l'Université Laval, 1996)
Le partage de l'emploi, conditions et avantages, étudié à partir de l'exemple de Bell Canada et celui de Volkswagen en Allemagne.
Google-Books-ID: fBo7MpV9MBIC

Riding the Wave of Trade: The Rise of Labor Regulation in the Golden Age of Globalization - Huberman, Michael; Meissner, Christopher M. (The Journal of Economic History, 2010)
The received view pins the adoption of labor regulation before 1914 on domestic forces. Using directed dyad-year event history analysis, we find that trade was also a pathway of diffusion. Market access served as an important instrument to encourage the diffusion of labor regulation. The type of trade mattered as much as the volume. In the European core, states emulated the labor regulation of partners because intra-industry trade was important. The New World exported less differentiated products and pressures to imitate were weak.

Occupational Gender Segregation and Women's Wages in Canada: An Historical Perspective - Fortin, Nicole M.; Huberman, Michael (Canadian Public Policy / Analyse de Politiques, 2002)
Nous traçons un portrait de l'évolution de la ségrégation professionnelle selon le sexe au 20ième siècle, et de ses conséquences sur la condition féminine dans le marché du travail. Dans la première partie du 20ième siècle, la ségrégation professionnelle hiérarchique ou verticale a considérablement décliné alors que les travailleuses quittaient les emplois de domestique et du secteur manufacturier en faveur des emplois de bureau. Ceci créa néanmoins une importante ségrégation professionnelle horizontale qui persiste jusqu'à aujourd'hui. Pour étudier les effets de la ségrégation professionnelle sur l'écart salarial selon le sexe, nous présentons une technique de décomposition qui divise l'écart salarial en deux composantes: l'une due aux différences intra-occupations et l'autre due aux différences inter-occupations. Depuis le début des années 90, la composante intra-occupation est prédominante. /// We document the evolution of occupational gender segregation and its implications for women's labour market outcomes over the twentieth century. The first half of the century saw a considerable decline in vertical segregation as women moved out of domestic and manufacturing work into clerical work. This created a substantial amount of horizontal segregation that persists to this day. To study the effects of occupational segregation on the gender gap, we introduce a decomposition technique that divides the gap into between-occupation and within-occupation components. Since the 1990s the component attributable to within-occupation wage differentials has become predominant.

Bend it like Beckham: Hours and wages across forty-eight countries in 1900 - Huberman, Michael; Lewis, Frank D. (Queen's Economics Department Working Paper, 2007)
Based largely on the Fifteenth Annual Report of the U.S. Department of Labor, published in 1900, we have built a sample of wages and hours for roughly fifty countries in six continents that covers the period 1890-1900. The Report, which is drawn from official (national) publications, gives information on normal or usual hours and earnings per week at the establishment level. To our knowledge, this is the most extensive data set of its kind totaling about 15,000 observations. We combine the data set with other country-specific evidence to derive implications about labour supply. The data reveal a cross-country supply curve that was markedly backward-bending. In addition, for a given wage level, we find a positive relation between a country's per-capita income and work hours. We interpret the patterns by proposing a standard utility function in consumption and hours of work, where a minimal level of consumption is introduced as a constraint. We interpret that minimum more broadly than biological subsistence. Rather minimal consumption is assumed to increase with the average income of a country. We also explore the possible role of climate in affecting the consumption constraint. Given the size of the data set, although coverage is uneven, we are able to estimate labour supply curves within countries and regions, in addition to making overall comparisons of work hours across countries. Our preliminary work suggests that a consumption constraint played a key role in the negative relation between wages and hours of work within countries, and that across countries higher average incomes, which effectively raised the constraint, promoted greater work hours.

A “zero tolerance for overtime” increases surgical per case costs - Tessler, Michael J.; Kleiman, Simcha J.; Huberman, Michael M. (Canadian Journal of Anaesthesia, 1997)
One technique which some hospitals have used in an attempt to control Operating Room costs is a “zero tolerance for overtime” policy. We used a case cost analysis to determine if this policy was always cost effective.
Keywords: Canada Statistic; Frais; Labour Cost; Post Anaesthesia Care Unit; Zero Tolerance

Chapter 3 When Labour Hires Capital: Evidence from Lancashire, 1870–1914 - Huberman, Michael (Experiencing Wages, 2003)

Globalisation everywhere, except in the growth numbers: Pessimism reaffirmed? - Meissner, Christopher; Oosterlinck, Kim; Huberman, Michael (CEPR, 2015)
Understanding the relationship between trade and growth is still at the core of the economics profession. This column seeks to identify the pathways by which globalisation affects economic growth looking at the case of Belgium in the decades preceding the First World War. It argues that the collapse in fixed export costs promoted the entry of uncompetitive firms into export markets and as the trade component of GDP rose, the share of high performing firms contracted, slowing growth.

Économie de la réputation commerciale. Une histoire du crédit marchand à Montréal au 19e siècle - Lapalme, Alexandre (Université de Montréal, 2022)
This thesis examines the credit records between 1847 and 1872 of the Montreal branch of the Mercantile Agency, among the most important credit bureaus in 19th century North America. The 19th century saw the acceleration of transatlantic trade. Montreal, located between Great Britain and the United States, was at the crossroads of the economic expansion. In this period, commonly referred to as the transition to capitalism, the legal, commercial and financial institutions of the metropolis were forced to adjust. In the financial sector, the state was compelled to adopt bankruptcy laws to lessen the negative effects of bad debts and to encourage and support the spread of commercial credit. However, because of limited accessibility, and the complexity and costs of the procedure, the laws were unable to fully guarantee the recovery of loans and were deemed unsatisfactory by the business community. The thesis claims that the emergence of credit agencies responded to the needs of the business community to address problems of information asymmetry. These agencies, like the Mercantile Agency, established a type of self-regulation of commercial credit. They provided information on risk to lenders. To a large extent, the information gathered represented the opinion of the Montreal merchant community. The credit offices of the Mercantile Agency used this information to generate rankings of the credit worthiness of merchants. The information was disseminated to the Agency’s network of subscribers. In this fashion, the Agency contributed to the construction of an economy of reputations. The research, which is inspired by contributions to the new history of capitalism, explores the effects of the construction of the economy of reputations on the relationship between lenders and borrowers. I find that the structure of the relationship favored creditor over debtors. The chapters of the thesis describe the role of reputation in the creditor-debtor relationship, the determinants adopted to measure credit worthiness, and the tensions and conflicts that emerged in the economy of reputations.
Keywords: 19e siècle; 19th century; =CL; Bankruptcy laws; Bureaux de crédit; Canadian history / Histoire du Canada (UMI : 0334); Capitalism; Capitalisme; Commerce; Commercial credit; Credit bureaus; Crédit marchand; Histoire; History; Lois sur les faillites; Montreal; Montréal; Reputation; Réputation

Technology and Geography in the Second Industrial Revolution: New Evidence from the Margins of Trade - Huberman, Michael; Meissner, Christopher M.; Oosterlinck, Kim (The Journal of Economic History, 2017)
Belle Époque Belgium recorded an unprecedented trade boom. Exploiting a new granular trade dataset, we find that the number of products delivered abroad and destinations serviced more than doubled in less than 40 years. To explain this remarkable achievement, we study the relationship between trade costs and the intensive and extensive margins of trade. The establishment of a foreign diplomatic network that lowered beachhead costs and enabled the entry of new products was an essential fact of the trade boom. Interestingly, the expansion in trade in certain sectors did not translate into faster productivity growth. We offer some explanations.

Étude comparative de la pensée économique canadienne-française et canadienne-anglaise durant l'entre-deux-guerres - Belhumeur-Gross, Christian (Université de Montréal, 2015)
L’entre-deux-guerres représente une période charnière dans l’évolution de la pensée économique au Canada. Le contexte économique et social des années 1920-1940 est des plus favorables au foisonnement de nouvelles idées et de nouvelles approches. Face à la crise et à l’urgence d’en sortir, les économistes, les intellectuels et les milieux politiques commencent à se questionner sérieusement sur les dysfonctions du capitalisme et de l’économie de marché. Pénétrée par des courants émergents, dont le keynésianisme et le corporatisme, et en parallèle avec une discipline économique en pleine formation, la pensée économique évolue considérablement durant ces années alors que les économistes s’interrogent sur les orientations des politiques gouvernementales. L’étude des deux grandes revues d’économie-politique, L’Actualité économique et le Canadian Journal of Economics and Political Sciences, ainsi que l’analyse des travaux des principaux économistes de l’époque, incarnés par Harold A. Innis, W. A. Mackintosh, Esdras Minville et Édouard Montpetit, révèlent les nouvelles orientations face aux problèmes qui confronte le Canada.
Keywords: Canada; Canadian Journal of Economics and Political Science; Corporatism; Corporatisme; Economic History; Economic Thought; Esdras Minville; Harold A. Innis; Histoire économique; History - Canadian / Histoire - Canadienne (UMI : 0334); Keynesianism; Keynésianisme; L'Actualité économique; Pensée économique; W. A. Mackintosh; Édouard Montpetit

Labor Movements - Huberman, Michael (The Cambridge history of capitalism, 2014)

A British food puzzle, 1770–18501 - Clark, Gregory; Huberman, Michael; Lindert, Peter H. (The Economic History Review, 1995)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1468-0289.1995.tb01416.x

Smooth sailing: market integration, agglomeration, and productivity growth in interwar Brazil - Badia-Miró, Marc; Carreras-Marín, Anna; Huberman, Michael (European Review of Economic History, 2023)
Leveraging an original dataset on coastal shipping and invoking a new economic geography framework, we study the effects of domestic and international trade costs on industrial concentration and productivity growth in interwar Brazil. In the great wave of globalization before 1914, international trade costs were low and domestic costs high. Economic activity was dispersed along the coastline. The interwar period saw a reversal: international costs surged and domestic costs declined. Economic activity was increasingly concentrated in São Paulo. Agglomeration economies enabled productivity growth in the 1930s, mostly in durable and capital goods.
Number: 1